5-DOF Dynamic Model of Vehicle Shimmy System with Clearance at Universal Joint in Steering Handling Mechanism. (2013) - Lu, Jianwei; Xu, Yi; Hu, Chen; Vakakis, Alexander F.; Bergman, Lawrence A.
Abstract : 5-DOF dynamic model of vehicle shimmy system with clearance in universal joint of steering handling mechanism is presented. The sub model of cross shaft universal joint with clearance is built based on Hertz' theory, and two-state model is applied to describe the contact force. The sub model of the universal joint is combined with the simplified dynamic model of steering system, and a 5-DOF dynamic model of vehicle shimmy system with consideration of assembling clearance in universal joint of steering handling mechanism is presented. Based on this model, numerical analysis is carried out to evaluate the influence of clearance in universal joint on the dynamic behavior of the vehicle shimmy system. The results show that the clearance and some other parameters, such as vehicle speed, have coupled contribution to the dynamic behavior of the vehicle shimmy system. The conclusions provide theoretical basis for effective attenuation of vehicle shimmy, especially for those in-service vehicles.